Answer:
(x - 1)² + (y + 1/2)² = 65/4
Step-by-step explanation:
Given: the endpoints of the diameter are (3, 3) and (-1, -4). a( To determine the center of this circle, find the midpoint of the line segment connecting these two points:
3 - 1
x = -----------
2
and
-1
y = ----------
2
The center is at x = 1 and y = -1/2: (1, -1/2).
b) The radius is half the diameter. The diameter is the distance between the two endpoints given, that is, the distance between (-1, -4) and (3, 3):
diameter = √(4² + 7²) = √(16 + 49) = √65; therefore,
radius = (1/2)√65.
square of the radius = r² = 65/4
The general equation of a circle with center at (h, k) and radius r is
(x - h)² + (y - k)² = r². In this case, the equation is:
(x - 1)² + (y + 1/2)² = 65/4
Answer:
1. D
2. F
3. B
4. A
5. A
6. F
Step-by-step explanation:
Solve for X
The correct answer is option B which is mixture B will have the highest ratio of blue paint.
<h3>What is a ratio?</h3>
In mathematics, ratios are used to determine the relationship between two numbers it indicates how many times is one number to another number.
<h3 />
The given ratios are:-
Mixture A = ![\dfrac{5}{12} = 0.41](https://tex.z-dn.net/?f=%5Cdfrac%7B5%7D%7B12%7D%20%3D%200.41)
Mixture B = ![\dfrac{6}{6}= 1](https://tex.z-dn.net/?f=%5Cdfrac%7B6%7D%7B6%7D%3D%201)
Mixture C = ![\dfrac{4}{12}= 0.33](https://tex.z-dn.net/?f=%5Cdfrac%7B4%7D%7B12%7D%3D%200.33)
Mixture B = ![\dfrac{5}{6}=0.83](https://tex.z-dn.net/?f=%5Cdfrac%7B5%7D%7B6%7D%3D0.83)
Here the ratio of mixture B is the highest among all the options available.
Therefore the correct answer is option B which is mixture B will have the highest ratio of blue paint.
To know more about ratios follow
brainly.com/question/2328454
#SPJ1
Answer:
51
Step-by-step explanation:
area of the triangle= 1/2 (6-3)(13-7)
=1/2 (3)(6)
=9
area of rectangle= 6×7
= 42
therefore, area of shape = 42+9
=51
Answer:
y= (-1/2)x+(5/2)
Step-by-step explanation:
equation point slope
(y-y1)=m(x-x1)
y-3 = -1/2(x+1) add -3 to both sides and distribute
y=( -x/2) +(-1/2)+3 rewrite 3 as 6/2
y=(-1/2)x +(-1+6/2) solve
y= (-1/2)x+(5/2)